The Association between Helicobacter pylori Seropositivity and Bone Mineral Density in Adults - Jinke Huang; Zhihong Liu; Jinxin Ma; Jiali Liu; Mi Lv; Fengyun Wang; Xudong Tang (Hindawi Limited, 2022)
Objectives. Current evidence on the associations between Helicobacter pylori (H. pylori) infection and bone mineral density (BMD) is conflicting. Therefore, a nationally representative sample of adults was analyzed to investigate the associations of H. pylori seropositivity and BMD in this study. Methods. A retrospective cross-sectional study was conducted with 2555 subjects aged 40-85 years in the US National Health and Nutrition Examination Survey (NHANES) 1999-2001. Multivariable logistic regression models were performed to evaluate the associations between H. pylori seropositivity and BMD. Subgroup analyses stratified by sex, age, race, and body mass index (BMI) were performed. Results. No association was found between H. pylori seropositivity and BMD (β=0.006, 95% CI: -0.003 to 0.015, P=0.177). In the subgroup analyses stratified by age, a positive association was observed between the H. pylori seropositivity and total BMD among subjects aged 40-55 years (β=0.018, 95% CI: 0.004 to 0.033, P=0.012); in the subgroup analyses stratified by sex, a positive association was observed between the H. pylori seropositive and total BMD in male (β=0.019, 95% CI: 0.007 to 0.032, P=0.003); in the subgroup analyses stratified by age and sex, the total BMD was higher in men aged 40-55 years with H. pylori seropositive than those with H. pylori seronegative (β=0.034, 95% CI: 0.013 to 0.056, P=0.002). Conclusions. In conclusion, no association between H. pylori seropositive and total BMD was demonstrated among most middle-aged and elderly adults. H. pylori infection may not be one key factor in the loss of BMD.